Intraperitoneal Chemotherapy Using Fluorouracil Implants Combined With Radical Resection and Postoperative Adjuvant Chemotherapy for Stage III Gastric Cancer: A Multi-Center, Randomized, Open-Label, Controlled Clinical Study - Xu, Yan; Zhang, Rupeng; Li, Chunfeng; Sun, Zhe; Deng, Jingyu; Wang, Xiaona; Ding, Xuewei; Wang, Baogui; Xue, Qiang; Ke, Bin; Zhan, Hongjie; Liu, Ning; et al. (Frontiers in Oncology, 2021)
Background Reducing peritoneal recurrence after radical surgery is an important choice to improve the prognosis of patients with advanced gastric cancer. Intraoperative intraperitoneal chemotherapy has the potential to be a promising treatment strategy. In the present study, we conducted a multi-center, randomized, controlled clinical study to evaluate the efficacy and safety of intraoperative intraperitoneal chemotherapy using sustained-release fluorouracil implants plus radical gastrectomy and adjuvant chemotherapy for cTNM stage III gastric cancer. Methods The patients were randomized into intraperitoneal chemotherapy group (sustained-release fluorouracil implants administration after standard D2 radical gastrectomy, and followed by XELOX adjuvant chemotherapy) and control group (standard D2 radical gastrectomy, and followed by XELOX adjuvant chemotherapy). A total of 122 patients from three centers were enrolled from September 2015 to February 2017. Results One hundred and two eligible patients completed the treatment course. The median follow-up time was 41.7 months (36.1–52.9 months). The 3-year progression-free survival rate and overall survival of patients in the intraperitoneal chemotherapy group were 43.9% and 49.1%, respectively, which were significantly better than those of the control group, 31.0% and 38.4%. In the intraperitoneal chemotherapy group, the number of cases with peritoneal recurrence was significantly less than that of the control group, 9 cases (17.3%) vs. 19 cases (44.2%). There were neither significant differences between the groups in the incidence of hematogenous metastasis, lymph node metastasis, nor local metastasis. Conclusion For cTNM stage III gastric cancer, intraoperative sustained-release fluorouracil implants after radical resection combined with postoperative adjuvant chemotherapy, could significantly reduce the risk of peritoneal recurrence and prolong PFS. Clinical Trial Registration https://clinicaltrials.gov/, identifier (NCT02269904).